Authoritarianism and Mass Political Preferences in Times of COVID-19: The 2020 New Zealand General Election - Vowles, Jack (Frontiers in Political Science, 2022)
The adoption of restrictive policies to contain the spread of COVID-19 has led many to fear the authoritarian implications of excessive government powers over compliant publics. One of the strongest government responses took place in New Zealand, followed only a few months later by the landslide election victory of the Labour Party, the dominant party in the pre-election coalition. This article tests a claim that authoritarian dispositions were mobilized into an authoritarian electoral response. It finds no evidence of a significant shift toward authoritarianism. Authoritarianism did not increase in the mass public and liberals were more likely than authoritarians to approve of the government response and to move toward a vote for the Labour Party, a tendency most apparent among liberals on the right. To the small extent that some disposed toward authoritarianism did move toward the government, they tended to be on the left and/or have higher than average trust in politicians.